Reasons for repeated emergency department visits among community‐dwelling older adults with dementia in Ontario, Canada. Issue 6 (3rd March 2022) - Jones, Aaron; Maclagan, Laura C.; Watt, Jennifer A.; Schull, Michael J.; Jaakkimainen, Liisa; Swayze, Sarah; Guan, Jun; Bronskill, Susan E.
Abstract: Background: Community‐dwelling older adults living with dementia visit the emergency department (ED) more frequently than other older adults, but research on the reasons for repeated visits is lacking. We examined the rate of repeated ED visits and reasons for visits in a cohort of individuals with dementia. Methods: We conducted a population‐based retrospective cohort study of community‐dwelling older adults (≥66 years) living with dementia in Ontario, Canada, who visited the ED and were discharged home between April 1, 2010, and March 31, 2019. We calculated the proportion of the population with one, two, and three or more repeat ED visits within 1 year of the baseline visit and the categorized the reason for the visits. Results: Our cohort contained 175, 863 individuals with dementia who visited the ED at least once. Overall, 66.1% returned at least once to the ED within 1 year, 39.4% returned twice, and 23.5% returned 3 or more times. Visit reasons were heterogenous and were most frequently related to general signs and symptoms (25.3%) while being infrequently due to cognitive or behavioral reasons (5.9%). Individuals typically visited for different reasons across successive visits. Conclusions: Community‐dwelling older adults with dementia who visited an ED were very likely to return to the ED within a year, with a substantial proportion visiting multiple times. The high frequency of repeated visits for different reasons highlights the complexity of caring for this population and indicates greater need for comprehensive community and primary care as well as timely communication between the ED and the community.